Presence of parent, gender and emotional valence influences preschoolers' PFC processing of video stimuli - Durnford, Justin R. (2022)
Unprecedented increases in child exposure to diverse videos has resulted in a need to understand how children process videos. While children show distinct activations in the prefrontal cortex (PFC) when presented with children's movies, multiple factors influence child neural response to screen media, namely, presence of a specific parent, gender differences and emotional valence. Sixty-two children (37 boys) aged 3 to 4 and their parents (33 mothers, 29 fathers) were recruited fora joint video task involving three video clips that varied in emotional valence while children's neural responses were measured using functional near-infrared spectroscopy. We found a significant interaction effect between emotional valence and gender. Children who engaged in joint-viewing with their fathers also showed significantly stronger PFC activity than with their mothers, regardless of emotional valence of video. Our findings suggest how, at a PFC level, different factors interact and influence the joint-viewing experience amongst parent–child dyads.